2016
DOI: 10.1108/josm-11-2015-0364
|View full text |Cite
|
Sign up to set email alerts
|

The impact of customer value types on customer outcomes for different retail formats

Abstract: Purpose – The purpose of this paper is to profile grocery retailers in terms of seven value types based on Holbrook’s value typology; to link these value types to three key outcomes (i.e. satisfaction, repurchase intention, and word-of-mouth); and to evaluate the impact of the retail format on performance and importance of the seven value types. Design/methodology/approach – For each retail format, the authors administered a consumer sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 95 publications
6
56
0
4
Order By: Relevance
“…However, limited studies have examined the influence of CPV on repurchase intention among the CHA users. Chiu et al (2014) confirmed that utilitarian and hedonic value were significantly associated with repurchase intention, while Willems et al (2016) provided evident that FVP (efficiency), SV, and EV (aesthetics and play) predicted repurchase intention but FVQ (product and service excellence) did not predicted repurchase intention. This study examined the influence of second-order formative CPV, with FVP, FVQ, SV, EV, and CV as the first-order, on repurchase intention among HMP users.…”
Section: Repurchase Intentionmentioning
confidence: 74%
See 1 more Smart Citation
“…However, limited studies have examined the influence of CPV on repurchase intention among the CHA users. Chiu et al (2014) confirmed that utilitarian and hedonic value were significantly associated with repurchase intention, while Willems et al (2016) provided evident that FVP (efficiency), SV, and EV (aesthetics and play) predicted repurchase intention but FVQ (product and service excellence) did not predicted repurchase intention. This study examined the influence of second-order formative CPV, with FVP, FVQ, SV, EV, and CV as the first-order, on repurchase intention among HMP users.…”
Section: Repurchase Intentionmentioning
confidence: 74%
“…In those studies that confirmed a positive relationship between FVQ and behavior or intention, FVP was found to be insignificant (Suki, 2016;Yang & Lin, 2017). Contrarily, those studies that confirmed FVP had a significant positive relationship with the dependent variables found that FVQ was insignificant (Khan & Mohsin, 2017;Willems, Leroi-Werelds & Swinnen, 2016). Undoubtedly, FV is an important value perceived by CHA users (Dodds et al, 2014).…”
Section: Functional Valuementioning
confidence: 96%
“…A szakirodalom és az előzetes várakozások alapján arra számítunk, hogy a magyarországi kínálat meglehetősen szűkös, ahol jellemzően a nagy dél-európai termelő országok (Olaszország, Franciaország és Spanyolország) magas feldolgozottsági szintű (sajt-és húskészítmények) OFJ termékei a legjobban elérhetőek, kiegészülve magyar, illetve német termékekkel (ez utóbbit az indokolja, hogy mindhárom vizsgált élelmiszerlánc német tulajdonban van). (WILLEMS et al, 2016). Egy másik látványos változást jelentett az elmúlt években az, hogy a diszkont áruházak újrapozícionálták magukat, már nem feltétlenül csak a legolcsóbb áruházként akartak megjelenni a piacon.…”
Section: Anyag éS Módszer -Materials and Methodsunclassified
“…Aldi and Lidl were active in 28 European countries in 2016, with an average market share of 10%, but in Germany and Austria, for example, this figure was towards 35% and had been increasing since then [40]. In Belgium, a survey in 2013 showed that the discount stores possessed 42.6% of the food retail trade in the country [41].…”
Section: Characteristics Of Discountersmentioning
confidence: 99%
“…Discount stores offer fewer products, around 1300-1400 items, as opposed to the average 30,000 available in supermarkets [39], but the supply of these discounters is constant and changes less frequently than other types of stores. Another important feature of discount stores is that a significant part of their supply is private labelled product [41,44]. Discounters can have a better influence on the retail price of the private labelled products, which contributes to a different pricing strategy for discount stores [45].…”
Section: Characteristics Of Discountersmentioning
confidence: 99%